2019
DOI: 10.1002/acr.23721
|View full text |Cite
|
Sign up to set email alerts
|

Area‐Level Predictors of Medication Nonadherence Among US Medicaid Beneficiaries With Lupus: A Multilevel Study

Abstract: Among Medicaid beneficiaries with SLE, we observed significant effects of racial composition and hospital concentration on HCQ adherence. Interventions that acknowledge and address contextual factors should be considered to reduce high rates of nonadherence in vulnerable populations. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Lower educational level and greater disease activity are associated with increased intentional and non-intentional medication non-adherence. 11,12,20 None of the disease characteristics (disease activity, disease duration, number of comorbidities) were associated with measures of adherence also consistent with the existing literature. 15 Adherence rates for immunosuppressive medications were good (>80%) with rates for mycophenolate mofetil being slightly higher compared to azathioprine (87.7% vs. 83.3%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Lower educational level and greater disease activity are associated with increased intentional and non-intentional medication non-adherence. 11,12,20 None of the disease characteristics (disease activity, disease duration, number of comorbidities) were associated with measures of adherence also consistent with the existing literature. 15 Adherence rates for immunosuppressive medications were good (>80%) with rates for mycophenolate mofetil being slightly higher compared to azathioprine (87.7% vs. 83.3%).…”
Section: Discussionsupporting
confidence: 80%
“…Patients were recruited only at one site which is also a centre of excellence for SLE which could have contributed to more favourable outcomes. Perceived costs and evaluation of the healthcare system 20,52 and frequency of medication intake 17,52 that have been reported as predictors of adherence were not evaluated in the present study, nor were objective measures of medication adherence such as tablet counts, diary cards or drug levels. Data on patients’ trust and quality of relationship with their GPs with whom they may have more frequent contact were not collected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A literature review of medication utilisation in SLE found the percentage of non-adherent patients ranged from 43% to 75%, with studies consistently reporting that >50% of patients were non-adherent 28. Studies of specific SLE treatments, many of which are considered the cornerstone of SLE treatment (hydroxychloroquine, azathioprine, mycophenolate mofetil and immunosuppressive medications), have also consistently shown adherence rates of <25% and medication possession ratios well below the accepted threshold of 80% 29–32. Adherence may have been suboptimal due to hospitalisation as belimumab treatment may have been suspended.…”
Section: Discussionmentioning
confidence: 99%
“…Given the growing body of evidence indicating low treatment adherence in lupus [20,32,33], recent efforts have examined large Medicaid data to assess disparities in lupus medication adherence [34,35,36]. Among over 10 000 US Medicaid beneficiaries who met the case definition of SLE and initiated hydroxychloroquine, only 15% were classified as adherent [34]. Adherence was lower in geographic areas with higher percentages of black individuals [highest tertile OR 0.81 (0.69–0.96) versus lowest].…”
Section: Other Research Targeting High-risk Populations With Systemicmentioning
confidence: 99%